ANALISIS UPAYA PENCEGAHAN DAN PENYELESAIAN TINDAKAN SIDE STREAMING PADA PRODUK PEMBIAYAAN MIKRO DENGAN AKAD MURABAHAH BIL WAKALAH (STUDI KASUS BSI KCP PROBOLINGGO SUDIRMAN) - Natasya Risma Putri; Kustiana Arisanti; Hayatul Millah (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2023)
In several cases that have been found in several different places, the application of a murabaha contract accompanied by a wakalah contract in it has resulted in side-streaming actions by its customers. Where the existence of side-streaming actions carried out by the customer is considered to cause harm to the party concerned. However, it is different from what happened at BSI KCP Probolinggo Sudirman, where of all existing microfinance customers, there was no record of such side streaming actions. This research was conducted at BSI KCP Probolinggo Sudirman, with the aim of the research, namely to find out what are the efforts to prevent and resolve side streaming actions carried out on microfinance with a murabahah bil wakalah contract at BSI KCP Probolinggo Sudirman. This research is included in the type of case study research that uses a research approach in the form of descriptive qualitative methods. As well as using data collection methods in the form of observation, interviews, and literature studies. From the results of this study, it is known that efforts to prevent side streaming carried out by BSI KCP Probolinggo Sudirman include conducting BI checking analysis, 5C analysis, and making visits at the same time as requesting receipts/receipts of purchase of goods. As for the settlement steps that have been prepared, they are adjusted to the level of fraud committed by the customer.